Der hypertensive Notfall - Bönner, Gerd (DMW - Deutsche Medizinische Wochenschrift, 2017)
Hypertensive urgency and hypertensive emergency are associated with sudden, massive rise in blood pressure. An acute increase in blood pressure to values above 180/120 mmHg is considered critical. If not treated in time, it can quickly enter a life-threatening hypertensive emergency. The symptoms or organ damage determine the assessment as a crisis or an emergency. Rapid action is required. The therapy depends on the severity and the organ involvement. However the general principal is to avoid therapeutically induced hypotension.
Keywords: Hypertensive Krise; hypertensiver Notfall; Blutdrucksenkung; Antihypertensiva; Blutdrucktherapie